LINGUISTIC CHALLENGES AND ACADEMIC PERFORMANCE OF STUDENTS TRANSITIONING FROM SCHOOL TO AN ENGLISH MEDIUM UNIVERSITY IN KAZAKHSTAN - Sadykova, Assel (Nazarbayev University Graduate School of Education, 2022)
Kazakhstan is among the countries introducing English medium instruction (EMI) programs in higher education. Despite the rapid spread of EMI, students whose first language is not English have difficulty adjusting to an English-only environment due to their inadequate language skills. In particular, the research highlights the role of students’ school background as a significant source of linguistic challenges. Therefore, this study seeks to investigate linguistic challenges of students transitioning to an EMI university in Kazakhstan with regard to their prior English learning experience in school and the influence of these challenges on students’ academic performance at university.
Keywords: Academic Performance of Students